ANALISIS PREDIKSI KEBANGKRUTAN DENGAN ALTMAN Z-SCORE DAN DETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN BENEISH M-SCORE PADA PERUSAHAAN ASURANSI - Efendi Marbun (JURNAL CAFETARIA, 2022)
The potential for bankruptcy can be a starting point for companies to commit financial statement fraud due to financial pressure. Insurance companies are businesses that are vulnerable to bankruptcy because the nature of their business is influenced by public trust. This study aims to determine the relationship of potential bankruptcy with fraudulent financial statements as a result of financial pressure. This study uses secondary data in the form of financial statements of insurance companies listed on the Indonesia Stock Exchange for the period 2019-2021. This research method is descriptive research using a quantitative approach. The results of the study indicate that companies that are predicted to experience bankruptcy have an indication of the possibility of fraudulent Financial Statements as a result of financial pressure.